Competition and cooperation in a PFF game theoretic model of electrical energy trade - Dávid Csercsik (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
A cooperative game theoretic framework is introduced to study the behavior of cooperating and competing electrical energy providers considering price-preference rational consumers. We analyze the interactions of generators in an idealized environment described by a DC load flow model where the network is lossless and is operated by an independent regulator who ensures network stability and fulfillment of consumption needs while taking into account the preferences of consumers over generators. We assume an iterative process in which the generators publish their price offers simultaneously in each step, based on which the consumers preferences are determined. The model deals with network congestion and safety as not every generator-consumer matching is allowed to ensure the fault tolerant operation of the transmission system. To make the model as simple as possible we do not deal with transmission fees, the profit of the generators is determined as the difference between their income, and their production cost which is assumed to be linearly decreasing with the produced quantity. Any non-monopolistic proper subset of the generators may cooperate and harmonize their offered prices to increase their resulting profit. Since we allow the redistribution of profits among cooperating generators, a transferable utility game theoretic framework is used. Furthermore, as cooperation affects the outsiders as well, the resulting game is defined in partition function form. The model is able to demonstrate some interesting benefits of cooperation as well as the effect of market regulations and asymmetric information on the resulting profits and total social cost.
Keywords: C71; L14; L94; 330; partition function form games; electrical energy transmission networks; Stromnetz; Elektrizitätswirtschaft; Kooperatives Spiel; Wettbewerb; Unternehmenskooperation; Koalition; Asymmetrische Information; Regulierung